Mathematical modelling of macrophage functioning in inflammatory bowel disease - Jansen, JE (2020)
Macrophages play a central role in host defence and the orchestration of the immune response. Macrophage functioning defects contribute to the development of inflammatory bowel disease (IBD), in particular Crohn’s disease. Mechanistic understanding of IBD is needed to improve clinical care. We combined mathematical modelling with existing and novel experimental data to drive insight in the role of macrophages in IBD.